Turkish Mothers’ Use of Complementation in Storytelling - Hande ILGAZ; Aslı ALTAN; Serap HAŞİMOĞLU ERTAŞ (Dilbilim Araştırmaları Dergisi)
This study investigated whether the amount and types of nominalizing complements Turkish speaking mothers use in storytelling vary by their preschool children’s age. Eighty-five middle-class mothers narrated a wordless storybook to their children (36 to 72 months). Mothers’ story-related talk was coded for complements formed with the nominalizing suffixes -mA, -mAK, -DIK, -(y)AcAK. These complement structures were then coded for whether they contained mental state verbs. Contrary to expectation, the results demonstrated no difference in mothers’ use of complementation by their children’s age. However, there were significant differences in suffix type. -mAK constructions were found to be the most frequently used complement type, followed by -DIK, -mA, and -(y)AcAK constructions. In addition, complement structures that contained a mental state verb as the complement verb were found to be the least frequent. The results show remarkable similarities with findings from the acquisition of complementation literature and are discussed in terms of their implications.